2018
DOI: 10.1186/s13018-018-0816-z
|View full text |Cite
|
Sign up to set email alerts
|

The anteroposterior axis of the tibia is adjusted to approximately a right angle to the anterior pelvic plane in the standing position in patients with hip dysplasia similar to normal subjects: a cross-sectional study

Abstract: BackgroundWe previously described that the anteroposterior (AP) axis of the tibia is approximately perpendicular to the transverse axis of the anterior pelvic plane (APP) in the standing position in healthy subjects. The purpose of this study was to investigate the rotational alignment between the APP and clinical epicondylar axis and the AP axis of the tibia relative to pelvic coordination in the standing position in normal subjects and in women with developmental dysplasia of the hip (DDH) to aid decision ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Several investigations described the morphological features with regard to the acetabulum and the proximal femur in patients with DDH to investigate the etiology and/or prevention of osteoarthritis of the hip [35]. However, morphological deformities in DDH not only appear in the hip joint but also in the knee joint, such as “coxitis knee” [6, 7]. However, few reports have investigated the knee joints and their morphology in DDH patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several investigations described the morphological features with regard to the acetabulum and the proximal femur in patients with DDH to investigate the etiology and/or prevention of osteoarthritis of the hip [35]. However, morphological deformities in DDH not only appear in the hip joint but also in the knee joint, such as “coxitis knee” [6, 7]. However, few reports have investigated the knee joints and their morphology in DDH patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the knee rotation angle (KRA) has previously been shown to be significantly larger in patients with DDH than in normal healthy subjects, and there was no significant correlation between femoral neck anteversion and KRA when using the three-dimensional (3D) method [7]. Li et al [6] described that the width of the femoral condyles was smaller and observed greater asymmetry at the medial and lateral condyles in DDH patients than in normal hips.…”
Section: Introductionmentioning
confidence: 99%
“…Data on the subjects were described regarding the spatial alignment of the femur and tibia from a previous study [14][15][16] and were used with written permission. The participants had no back or knee symptoms.…”
mentioning
confidence: 99%
“…No abnormalities were observed on the plain radiographs of the hip, knee, or spine. CT was performed on all subjects to reconstruct the 3D bone models of the pelvis and femur, as described previously [14][15][16] . A multislice CT scanner with a 64-row detector (Aquilion64™; Toshiba Medical Systems, Otawara, Tochigi, Japan) acquired approximately 500 slices (slice thickness, 1.25 mm) from each participant.…”
mentioning
confidence: 99%
“…The tibial rotational alignment: the knee rotation angle (KRA: the angle between the perpendicular line of the trans-epicondylar axis and the Akagi's line) and the pelvis-tibia angle (PTA: the angle between the tangent to the posterior ischial spine and the Akagi's line) [5,24].…”
mentioning
confidence: 99%